HTLV-1 and HTLV-2: highly similar viruses with distinct oncogenic properties - Ciminale, Vincenzo; Rende, Francesca; Bertazzoni, Umberto; Romanelli, Maria G. (Frontiers in Microbiology, 2014)
HTLV -1 and HTLV-2 share broad similarities in their overall genetic organization and expression pattern, but they differ substantially in their pathogenic properties. This review outlines distinctive features of HTLV-1 and HTLV-2 that might provide clues to explain their distinct clinical outcomes. Differences in the kinetics of viral mRNA expression, functional properties of the regulatory and accessory proteins, and interactions with cellular factors and signal transduction pathways are discussed.